Patent cooperation treaty yearly review 2021 the international patent system (WIPO Publication, 2021)
Comprehensive facts, figures and analysis of the international patent system. Special theme: A first insight into the impact of the COVID-19 pandemic on PCT applications. Datos completos, cifras y análisis del sistema internacional de patentes. Tema especial: Una primera visión del impacto de la pandemia de COVID-19 en las solicitudes PCT